Grain boundary-mediated nanopores in molybdenum disulfide grown by chemical vapor deposition - Duesberg, Georg; Mc Evoy, Niall (Royal Society of Chemistry, 2017)
Molybdenum disulfide (MoS2) is a particularly interesting member of the family of two-dimensional (2D) materials due to its semiconducting and tunable electronic properties. Currently, the most reliable method for obtaining high-quality industrial scale amounts of 2D materials is chemical vapor deposition (CVD), which results in polycrystalline samples. As grain boundaries (GBs) are intrinsic defect lines within CVD-grown 2D materials, their atomic structure is of paramount importance. Here, through atomic-scale analysis of micrometer-long GBs, we show that covalently bound boundaries in 2D MoS2 tend to be decorated by nanopores. Such boundaries occur when differently oriented MoS2 grains merge during growth, whereas the overlap of grains leads to boundaries with bilayer areas. Our results suggest that the nanopore formation is related to stress release in areas with a high concentration of dislocation cores at the grain boundaries, and that the interlayer interaction leads to intrinsic rippling at the overlap regions. This provides insights for the controlled fabrication of large-scale MoS2 samples with desired structural properties for applications.
Keywords: Atomic-scale analysis; Chemical vapor depositions (CVD); Interlayer interactions; Molybdenum disulfide; Nanopore formation; Polycrystalline samples; Tunable electronic properties; Two Dimensional (2 D)